Limb Salvage and Functional Outcomes following Free Tissue Transfer for the Treatment of Recalcitrant Diabetic Foot Ulcers - Lu, Jocelyn; DeFazio, Michael V.; Lakhiani, Chrisovalantis; Abboud, Michel; Penzler, Morgan; Elmarsafi, Tammer; Kim, Paul J.; Attinger, Christopher E.; Evans, Karen K. (Journal of Reconstructive Microsurgery, 2019)
Background Recent evidence documenting high success rates following microvascular diabetic foot reconstruction has led to a paradigm shift in favor of more aggressive limb preservation. The primary aim of this study was to examine reconstructive and functional outcomes in patients who underwent free tissue transfer (FTT) for recalcitrant diabetic foot ulcers (DFUs) at our tertiary referral center for advanced limb salvage.Methods Between June 2013 and June 2016, 29 patients underwent lower extremity FTT for diabetic foot reconstruction by the senior author (K.K.E.). In all cases, microsurgical reconstruction was offered as an alternative to major amputation for the management of recalcitrant DFUs. Overall rates of flap survival, limb salvage, and postoperative ambulation were evaluated. The lower extremity functional scale (LEFS) score was used to assess functional outcomes after surgery.Results Overall rates of flap success and lower limb salvage were 93 and 79%, respectively. Flap failure occurred in two patients with delayed microvascular compromise. Seven patients in this series ultimately required below-knee amputation secondary to recalcitrant infection (n = 5), intractable pain (n = 1), and limb ischemia (n = 1). The average interval between FTT and major amputation was 8 months (r, 0.2–15 months). Postoperative ambulation was confirmed in 25 patients (86%) after a mean final follow-up of 25 months (r, 10–48 months). The average LEFS score for all patients was 46 out of 80 points (r, 12–80 points), indicating the ability to ambulate in the community with some limitations.Conclusion FTT for the management of recalcitrant DFUs is associated with high rates of reconstructive success and postoperative ambulation. However, several patients will eventually require major amputation for reasons unrelated to ultimate flap survival. These data should be used to counsel patients regarding the risks, functional implications, and prognosis of microvascular diabetic foot reconstruction.
Keywords: diabetic foot ulcer; free tissue transfer; limb salvage